The Role and Function of Koperasi Madura Multifarm Agromandiri in the Local Economy - Choirul Anam; Khoirotun Nisa; Mashudi (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2026)
Koperasi Madura Multifarm Agromandiri, located in Surabaya, plays a crucial role in supporting the local economy, particularly in the agriculture and agribusiness sectors. This cooperative serves as a platform for farmers and small businesses to access funding, marketing opportunities, and business mentoring. Upholding the principles of mutual cooperation and a people-centered economy, the cooperative enhances the welfare of its members through various programs, such as providing agricultural production facilities, entrepreneurship training, and broader distribution access. This article further explores the strategic role and key functions of Koperasi Madura Multifarm Agromandiri in driving regional economic growth and improving community welfare